Faktor-Faktor Yang Mempengaruhi Penerimaan Guru Menggunakan Google Classroom Dalam Pembelajaran Teradun Matematik - NAZRI, SEDI (Universiti Malaysia Sarawak, 2025)
Ministry of Education aspires to utilise the use of Information and Communications Technology (ICT) to improve the quality of learning in Malaysia and produce digital competence teachers throughout Malaysia Educational Blueprint 2013-2025 and Digital Education Blueprint. Among the initiative taken by the Ministry of Education to achieve the aspiration was by introducing Google Classroom platform for learning practice across the schools in Malaysia. However, past studies find that the level of acceptance and the use of Google Classroom among teachers in Malaysia is still low and uncomprehensive. Thus, this research aims to identify and determine the factors that influence teachers' acceptance of using Google Classroom in Blended Learning for Mathematics subject based on the UTAUT model. This study uses survey method and online questionnaires through Google Forms application for the data collection process. The respondents of this study consist of 288 teachers who teach Mathematics across primary school in Sarawak. The sampling techniques used are cluster sampling and proportionate random sampling. The data of this study was analyzed using IBM SPSS Statistics Version 27 and SmartPLS 4.0 software. Findings show that the level of teachers' perception of the factors that influence teachers' acceptance of using Google Classroom in Blended Learning for Mathematics subject across the primary schools in Sarawak is only at a moderate level. The findings of the study also show that Social Influence (SI), Facility Conditions (FC) and Attitude (ATT) have a positive and significant relationship with Teacher Acceptance (TA) to use Google Classroom in Blended Learning for Mathematics subject across the primary schools in Sarawak. On the other hand, Performance Expectancy (PE), Effort Expectancy (EE) and Learning Value (LV) do not have a positive and significant relationship to Teacher Acceptance (TA) to use Google Classroom in Blended Learning for Mathematics subject across the primary school in Sarawak. In addition, there is no significant difference in Teacher Acceptance (TA) to use Google Classroom in Blended Learning for Mathematics subject across the primary school in Sarawak based on gender, age group, years of experience in teaching Mathematics, school location and highest academic qualifications. The six predictor factors or independent variables (PE, EE, SI, FC, LV and ATT) contribute 73.5.8% of the variance to the TA variable. Theoretically, this study contributes by extending the existing knowledge and theory (UTAUT model) to three main dimensions, namely technological extension, population extension as well as the addition of new variables. In the aspect of empirical, this study presents a specific model which explains the factors that influence teachers' acceptance of using Google Classroom, especially among primary school mathematics teachers in Sarawak. On the practical perspective, the findings of the study are believed to provide useful input to various parties to plan, manage and evaluate the success of the implementation of Google Classroom initiatives, especially in primary schools in Sarawak.